The hunt for Jimmie Browne : an MIA pilot in World War II China - Willett, Robert L., 1926- (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"On Tuesday, November 17, 1942, aircraft CNAC # 60 climbed slowly toward the Himalayas, growing smaller and smaller until it finally faded from sight, never to be seen again--until seventy years later"--